Psychological correlates of body dissatisfaction in Swiss youth over a one-year study-period - Mueller, Verena M.; Forrer, Felicitas; Meyer, Andrea H.; Munsch, Simone (Frontiers in Psychology, 2024)
It is well known that young individuals often report pronounced negative perceptions and attitudes towards their own body or intense fear of being not muscular enough. There is much less data available, however, on the role of psychological mechanisms on these perceptions and attitudes, such as emotion regulation difficulties, correlates of alexithymia, and appearance-related rejection sensitivity. We therefore set out to assess associations between these psychological mechanisms, and body image as well as muscle dysmorphic symptoms. Our sample was recruited as part of a larger-scale study aiming at assessing correlates of mental health (with a focus on eating disorder symptoms) in German speaking Switzerland. The first wave (T1), starting in April 2021, included 605 participants (80% female, 19.6 ± 2.5 years) who completed the online-questionnaire and were reassessed in a second wave (T2), one year later. Results indicated that at both waves, emotion regulation difficulties [DERS-SF] and appearance-based rejection sensitivity [ARS-D] were both positively cross-sectionally associated with body dissatisfaction [BSQ-8C] and muscle dysmorphic symptoms [MDDI] at the first assessment time-point and one year later at follow-up assessment. Moreover, alexithymia [TAS-20] was positively cross-sectionally associated with muscle dysmorphic symptoms at both waves. We further observed high absolute and relative level stabilities for all variables involved across the one-year study period. Even though the effects for some associations were rather small, our findings underline the relevance of such mechanisms in the development of body dissatisfaction and to a lesser extent of muscle dysmorphia symptoms over the period of one year. Additional research is necessary to replicate these findings in other youth samples.